(untitled) (Academia Science Repository, 2023)
In the article future art and craft artist picture drawing such as professional in the cycle of preparation main issues seeing will be released. Study and of the demonstration process as the main content the place of still life and special to the role focusing on and this one of learning tasks ensure variability, teaching increase efficiency, his structure and content education level allow customization will give. graduation qualification increase In the article practical to students to teach in the process "still life painting" in the department of work main stages seeing will be released also still life picture on work study and creative that understood ie. natural to the environment aesthetic relationship issues solution to do Still life decorative picture using in describing graph activity issues academic to the picture than deeper understood and in the drawing conventions transfer duties own into takes this and professional orientation of students to solve creative problems due to will bring.